The Use of Genre Based Approach (GBA) to Improve Students’ Writing Descriptive Text - Amin Maulani (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2021)
The study aimed to found whether there were significant differences between those who are taught by using Genre Based Approach (GBA) and the students who are taught by using conventional to improve the students' writing descriptive text of the tenth-grade students. Some problems that become a reason for the student's difficulty in writing are the students unknown the way to begin the writing, (1) they were not able to generate their ideas, (2)they can not make a sentence well, (3) they were sometimes confused to make writing in a paragraph well appropriate with the generic structures, (4) the student's motivation is low. This study used quantitative research which used experimental method and quasi-experimental design. The population is 159 students, where 68 students selected chose as samples by purposive sampling. To collect the data, the students write descriptive text, then analyzed by using independent t-test SPSS 20. Furthermore, the writer concluded that the Alternatif Hypothesis (Ha) of this study is accepted and the Null Hypothesis (Ho) of this study is rejected. It means that, no significant differences between students who are taught by using the Genre Based Approach (GBA) and those who are taught by using conventional to improve the students' writing descriptive text of the tenth-grade students.